Common clinical skills : manual for pediatrics - Zhu Lihu Lihui Tan Lihong; Wan Li Xie Jianhui (China : Editorial Board Member, 2016)
The basic difference between children and adults is that children are in the constantly changing process of growth and development, and de size, proportion, composition adnd organ function of their body change ceaselessly and become mature gradually with the incresase of age.
Contents Part 1 Medical sckills Chapter 1 Physical assessment Chapter 2 Common skills Part 2 Nursing skill Chapter 3 Basic nursing Chapter 4 Therapeutic skills Part 3 Medical equipment procedure Chapter 5 Common medical equipment Part 4 Infection control Chapter 6 Infection prevention and control Referent list
Incluye Contents
Keywords: PEDIATRICS -- MANUAL